2017
DOI: 10.1038/s41598-017-09478-6
|View full text |Cite
|
Sign up to set email alerts
|

Turn-on Luminescent Probe for Hydrogen Peroxide Sensing and Imaging in Living Cells based on an Iridium(III) Complex–Silver Nanoparticle Platform

Abstract: A sensitive turn-on luminescent sensor for H 2 O 2 based on the silver nanoparticle (AgNP)-mediated quenching of an luminescent Ir(III) complex (Ir-1) has been designed. In the absence of H 2 O 2 , the luminescence intensity of Ir-1 can be quenched by AgNPs via non-radiative energy transfer. However, H 2 O 2 can oxidize AgNPs to soluble Ag + cations, which restores the luminescence of Ir-1. The sensing platform displayed a sensitive response to H 2 O 2 in the range of 0−17 μM, with a detection limit of 0.3 μM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Hydrogen peroxide (H 2 O 2 ), as the most representative of redox oxygen species studied in cellular environments, not only is involved in immune response, oxidative stress, and pathogen invasion but also performs as secondary messengers, playing important roles in essential cellular processes. , Therefore, detection of H 2 O 2 released from living cells is essential to fully understand its roles in cellular physiology, as well as providing reliable diagnosis of pathological conditions. Seminal contributions have demonstrated that numerous analytical approaches, for example, fluorescence, chemiluminescence, electrochemiluminescence, and electrochemical methods, can be utilized for fast and accurate detection of H 2 O 2 released from living cells. Generally, special and effective signal molecules (fluorescence probes, etc.)…”
mentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ), as the most representative of redox oxygen species studied in cellular environments, not only is involved in immune response, oxidative stress, and pathogen invasion but also performs as secondary messengers, playing important roles in essential cellular processes. , Therefore, detection of H 2 O 2 released from living cells is essential to fully understand its roles in cellular physiology, as well as providing reliable diagnosis of pathological conditions. Seminal contributions have demonstrated that numerous analytical approaches, for example, fluorescence, chemiluminescence, electrochemiluminescence, and electrochemical methods, can be utilized for fast and accurate detection of H 2 O 2 released from living cells. Generally, special and effective signal molecules (fluorescence probes, etc.)…”
mentioning
confidence: 99%
“…817 Ma and co-workers have developed a nanosensor for sensitive detection of H 2 O 2 . 818 The nanosensor utilizes AgNPs as a responsive unit and an iridium(III) complex (431) (Chart 193) as a signaling unit. The emission of the complex is effectively quenched upon adsorption onto the AgNPs due to efficient energy transfer.…”
Section: •−mentioning
confidence: 99%
“…Understanding the function and regulatory mechanisms of metalloproteinases may provide insights into the future development of diagnostic and therapeutic approaches (e.g. nanomaterials or metal-based probe targeting these enzymes) for chronic inflammatory diseases ( 20 24 ).…”
Section: Othersmentioning
confidence: 99%